Intrinsic Fluoride Tolerance Regulated by a Transcription Factor. (October 2020) - Lu, M.; Xiang, Z.; Gong, T.; Zhou, X.; Zhang, Z.; Tang, B.; Zeng, J.; Wang, L.; Cui, T.; Li, Y.
Fluoride facilitates the remineralization of dental hard tissues and affects bacterial activities. Therefore, it is extensively used as an anti-caries agent in clinical practice and daily life. Although some studies focused on understanding Streptococcus mutans' response to fluoride, the mechanism regulating intrinsic fluoride tolerance is not yet clear. Since the TetR family of transcription factors is associated with multidrug resistance, our aim was to evaluate whether they are related to fluoride tolerance in S. mutans . A mutant library including each S. mutans TetR gene was constructed and the transcription factor fluoride related transcriptional regulator (FrtR) was identified. The in-frame deletion of the S. mutans frtR gene resulted in decreased cell viability under fluoride in both the planktonic state and single-/dual-species biofilms. This in-frame frtR mutant was used for RNA-sequencing and the fluoride related permease gene ( frtP ) was found as 1 of the downstream genes directly regulated by FrtR. The recombinant FrtR protein was purified, and conserved DNA binding motifs were determined using electrophoretic mobility shift and DNase I footprinting assays. Finally, a series of mutant and complement strains were constructed to perform the minimum inhibitory concentration (MIC) assays, which indicated that frtP upregulation led to the increase of fluoride sensitivity. Collectively, our results indicate that FrtR is an important transcription factor regulating the frtP expression in S. mutans, thus affecting the intrinsic fluoride tolerance. Therefore, this study provides novel insights into a potential target to increase the S. mutans sensitivity to fluoride for a better prevention of dental caries.